Alimentos para el futuro (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
There is ample justification for concern about adequate food supplies for future generations of mankind, but this concern should be broadened to include the immediate problem of an adequate standard of living for the world's present population. The successful solution of the immediate problems would furnish the best background of experience for meeting those that will arise in the future. First steps include the acceptance by society of responsibilities for the extension of the benefits of education throughout the world and provision for the type of scientific, economic, social, political, and religious leadership necessary to assure food for all on a continuing basis. Striking improvements in the food supply can be readily made through the application of present knowledge, if the foregoing conditions are met. The rapid pace of modern science, both pure and applied, gives promise that future benefits may be much greater than those thus far experienced. Current advances do not signal the end of a technical road but rather that the great scientific developments still lie ahead. If we have the intelligence and wisdom to recognize human responsibilities and to make constructive use of our natural and human resources, we can look forward to a better world in the future and improved standards of living for all.